(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The concept is of great importance in Cognitive Linguistics, essentially serving as its central organizing principle. Its importance stems from its role as the bridge connecting language, thought, and experience. Concepts are central to understanding meaning in language. Researching how words map onto concepts, how metaphors work, and how context influences interpretation is crucial for improving communication and natural language processing. Understanding how concepts vary across cultures is essential for effective cross-cultural communication and for avoiding misunderstandings.